How Senegal created an enabling environment for nutrition: A story of change - Kampman, Halie; Zongrone, Amanda; Rawat, Rahul; Becquey, Elodie (Elsevier, 2017)
In the past 15 years, Senegal has made considerable progress in the fight against child undernutrition. To better understand how this was achieved, we reviewed 11 national policy documents published between 2001 and 2015, and interviewed 25 key-informants from the government, donor community, civil society, as well as 24 local service providers and 18 community members. We explored the commitment of actors and coherence between and within sectors. We linked this to changes in nutrition services experienced by communities. The key theme that emerged was the critical role of increased political commitment, materialized and maintained by a high-level national coordinating body for nutrition. The body actively facilitates multisectoral coherence in action for nutrition, overseeing the implementation of a national nutrition program, the effects of which are seen at the community level.